Approach to Developmental Delay: A Developing World Perspective - Puneet Choudhary; Biswaroop Chakrabarty (Preventive Medicine: Research & Reviews)
This review article provides an overview of epidemiology of developmental delay, with focus on developing countries and from preventive medicine perspective. It discusses common etiological factors, clinical evaluation and a management approach with available diagnostic tools and therapeutic strategies. Management of developmental delay is centered around early intervention with initiation of specific treatment wherever relevant. A holistic multidisciplinary approach that addresses the diverse needs of these children is essential to achieve optimum outcomes.